2020
DOI: 10.1038/s42003-020-1105-z
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome-wide association study for restless legs syndrome identifies new susceptibility genes

Abstract: Restless legs syndrome (RLS) is a common neurological condition, with a prevalence of 5–15% in Central Europe and North America. Although genome-wide association studies (GWAS) have identified some common risk regions for RLS, the causal genes have yet to be fully elucidated. We conducted a transcriptome-wide association study involving 15,126 RLS cases and 95,725 controls, from the most recent meta-analysis of GWAS, and gene expression weights of GTEx v7 and the CMC dorsolateral prefrontal cortex tissue panel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…At 61 loci, there was a single independent lead SNP as well as a single top-scoring gene. These included six known loci, strengthening previous reports (MEIS1, PTPRD, SKOR1, NTNG1, CADM1 and RANBP17) 3,4,[10][11][12][13] . Because drug repurposing is one of the fastest options for translating GWAS findings into patient care, we mapped the top-scoring genes against the druggable genome and identified 13 potential candidates targeted by existing compounds (Table 1).…”
Section: Sex-stratified Autosomal Gwas and Meta-analysessupporting
confidence: 76%
“…At 61 loci, there was a single independent lead SNP as well as a single top-scoring gene. These included six known loci, strengthening previous reports (MEIS1, PTPRD, SKOR1, NTNG1, CADM1 and RANBP17) 3,4,[10][11][12][13] . Because drug repurposing is one of the fastest options for translating GWAS findings into patient care, we mapped the top-scoring genes against the druggable genome and identified 13 potential candidates targeted by existing compounds (Table 1).…”
Section: Sex-stratified Autosomal Gwas and Meta-analysessupporting
confidence: 76%
“…We identified 21 associations for seven genes at the transcriptome-wide significant level (Figure 2c), of which four were not identified in the previous transcriptome-wide association study (TWAS) for RLS: GLO1 (6p21), ELFN1 (7p22.3), UBASH3B (11q24.1), and CAPNS1 (19q13) 52 . Consistent with previous findings, the expression of three known RLS genes, MEIS1 , SKOR1 , and MAP2K5, were also associated with RLS 52-54 . A fine-mapping analysis using the ‘Fine mapping Of CaUsal gene Sets’ (FOCUS) software (v.0.802) 35 prioritized SKOR1 , PTPRD-AS1 , PRMT6 , STEAP2 , and GTPBP10 as putative candidate genes for RLS with posterior probabilities of 0.69, 0.13, 0.06, 0.06, and 0.02, respectively (Supplementary Table 6).…”
Section: Resultsmentioning
confidence: 83%
“…To do so, we used two transcriptomic imputation approaches, FUSION 33 and S-PrediXcan 34 , and tested the differential expression of these gene models in 13 brain tissues (Table 3). We identified 21 associations for seven genes at the transcriptome-wide significant level (Figure 2c), of which four were not identified in the previous transcriptome-wide association study (TWAS) for RLS: GLO1 (6p21), ELFN1 (7p22.3), UBASH3B (11q24.1), and CAPNS1 (19q13) 52 . Consistent with previous findings, the expression of three known RLS genes, MEIS1, SKOR1, and MAP2K5, were also associated with RLS [52][53][54] .…”
Section: Gene-burden Analysismentioning
confidence: 83%
“…[ 3 ] To date, genome-wide association studies of RLS have identified 13 different genes in several communities in Northern Europe, These genes are represented by chromosome 6p21.2 (BTBD9), 2p14 (MEIS1), 9p24.1-p23 (PTPRD), 15q23 (MAP2K5/SKOR1), and 16q12.1 (TOX3/BC034767) mononucleotides. [ 16 , 17 ] In addition, recent studies have identified 7 additional major susceptibility loci for RLS: RLS1 at 12q12-q21, RLS2 at 14q13-q21, RLS3 at 9p24-p22, RLS4 at 2q33, RLS5 at 20p13, RLS6 at 19p13, and RLS7 at 16p12.1. [ 18 , 19 ] The pathophysiological functions of these genomic loci are yet to be defined, but their main functions appear to be related to the neural development of the limb during the embryonic period.…”
Section: Pathophysiologymentioning
confidence: 99%